Strategies to Incorporate Ground-Granulated Blast-Furnace Slag and Copper Slag into Ultrahigh-Performance Fiber-Reinforce Concrete - Parrón-Rubio, María Eugenia; García-Manrique-Ocaña, José Manuel; González-Herrera, Antonio; Pérez-García, Francisca; Rubio Cintas, María Dolores (ASCE-Library, 2022)
In this work, the feasibility of incorporating different industrial wastes in the production of ultrahigh-performance fiber-reinforced concrete (UHPFRC) is investigated. Five different blends of UHPFRC were produced, partially replacing coarse sand with copper slag (CS) and cement and/or silica fume with ground-granulated blast-furnace slag (GGBFS). The replacement percentages ranged between 50% and 60% in all cases. This study focuses on the development of an UHPFRC using waste without special treatments and available in the Andalusia, Spain, market to reduce the cost of concrete. An extensive experimental program was carried out to analyze workability and mechanical properties. Results obtained showed a significant reduction in environmental and economic cost without loss in the UHPFRC performance. One of the main conclusions was that partial replacement of GGBFS increased the compressive and flexural strength at later ages (matching the traditional UHPFRC at 28 days) even when a small decrease was observed at early ages. In addition, the partial replacement of coarse sand by CS resulted in a UHPFRC with a compressive and flexural strength similar to the traditional UHPFRC at different ages.
https://openpolicyfinder.jisc.ac.uk/id/publication/11572
Keywords: Cemento - Aditivos; UHPC; Elastic Modulus; Granulate Blast Furnace Slag; Copper slag; Compressive strength